Text classification using artificial neural networks - Lakshmi Prasanna, P; D.Rajeswara Rao, Dr (International Journal of Engineering and Technology, 2017)
Text Categorization is the process of classifying the text or documents into its corresponding categories which are defined previously. As the text or data is increasing enormously now-a-days it’s not possible to classify all the text documents manually hence its necessary to use some techniques or methods to classify the text automatically. In this paper we are using the ANN technique to classify the text, the purpose of choosing it, its advantages and its process is described in the further sections.